2012
DOI: 10.1124/jpet.111.188987
|View full text |Cite
|
Sign up to set email alerts
|

δ-Opioid Mechanisms for ADL5747 and ADL5859 Effects in Mice: Analgesia, Locomotion, and Receptor Internalization

Abstract: N,N-diethyl-4-(5-hydroxyspiro[chromene-2,4Ј-piperidine]-4-yl) benzamide (ADL5859) and N,N-diethyl-3-hydroxy-4-(spiro-[chromene-2,4Ј-piperidine]-4-yl)benzamide (ADL5747) are novel ␦-opioid agonists that show good oral bioavailability and analgesic and antidepressive effects in the rat and represent potential drugs for chronic pain treatment. Here, we used genetic approaches to investigate molecular mechanisms underlying their analgesic effects in the mouse. We tested analgesic effects of ADL5859 and ADL5747 in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
75
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(80 citation statements)
references
References 37 publications
1
75
0
Order By: Relevance
“…Although all three major types of opioid receptors (m, d, and k) are able to mediate analgesia and antinociception, they have different pharmacological activities. Recently, a prominent role of d-opioid receptors in chronic pain such as neuropathic pain and inflammatory pain was reported from studies using mutant animals and selective agonists (Nadal et al, 2006;Nozaki et al, 2012). In a neuropathic pain rat model, d-opioid receptor protein expression was increased compared with a control rat in the dorsal root ganglion (Kabli and Cahill, 2007).…”
Section: Introductionmentioning
confidence: 91%
“…Although all three major types of opioid receptors (m, d, and k) are able to mediate analgesia and antinociception, they have different pharmacological activities. Recently, a prominent role of d-opioid receptors in chronic pain such as neuropathic pain and inflammatory pain was reported from studies using mutant animals and selective agonists (Nadal et al, 2006;Nozaki et al, 2012). In a neuropathic pain rat model, d-opioid receptor protein expression was increased compared with a control rat in the dorsal root ganglion (Kabli and Cahill, 2007).…”
Section: Introductionmentioning
confidence: 91%
“…Although morphine is considered selective for m-opioid receptors, selective agonists of the other three members of the extended opioid receptor family (i.e., d-and k-opioid receptors, and nociceptin receptors) also functionally inhibit Ca V 2.2 channels (Gross and Macdonald, 1987;Moises et al, 1994;Motin et al, 1995;Morikawa et al, 1998;Toselli et al, 1999;Larsson et al, 2000;Yeon et al, 2004;Ruiz-Velasco et al, 2005;Evans et al, 2010). As in the case of m-opioid receptors, their activation induces analgesia in various animal models of pain (King et al, 1997;Darland et al, 1998;Field et al, 1999;Mika et al, 2001;Courteix et al, 2004;Nozaki et al, 2012). Although there are no clinically approved d-opioid-and nociceptin receptor-targeting analgesics, there is at least one k-opioid receptor agonist (pentazocine) that is used in humans as an analgesic.…”
Section: Ca V 2 Channel Pathophysiologymentioning
confidence: 99%
“…Neither compound produced convulsions. A subsequent study revealed that these two compounds were also effective in a neuropathic pain model and, unlike SNC80, did not produce receptor internalization (Nozaki et al, 2012).…”
mentioning
confidence: 99%